Relationship between knowledge level and medication adherence on blood pressure in elderly hypertension patients in Muara Enim community health center: A cross-sectional study - Anggraeni, Surti; Jamila, Jamila; Nurfadila, Lutfi; Noviana, Marta Anggun; Agustina, Eci (Lentera Perawat, 2025)
Background: Hypertension is a global health problem with a high prevalence, particularly among the elderly, and carries a significant risk of serious complications. Adequate knowledge and adherence to antihypertensive medication are essential factors in controlling blood pressure. Objective: To determine the relationship between the level of knowledge and medication adherence with blood pressure among elderly patients with hypertension in the working area of Muara Enim Primary Health Center in 2024. Methods: This study employed a quantitative analytic design with a cross-sectional approach. A total of 30 elderly women with hypertension were selected using purposive sampling based on inclusion criteria. Data on knowledge and adherence were collected using a structured questionnaire, while blood pressure was measured using an aneroid sphygmomanometer. Data were analyzed using univariate and bivariate methods, with the independent t-test applied at a significance level of p < 0.05. Results: Of the total respondents, 43.3% had good knowledge and 56.7% had poor knowledge. Medication adherence was evenly distributed, with 50% adherent and 50% non-adherent. The mean systolic blood pressure was 165.33 mmHg (SD 11.25) and diastolic was 95.87 mmHg (SD 5.96). Knowledge was significantly associated with diastolic blood pressure (p = 0.025) but not with systolic blood pressure (p = 0.098). Adherence was significantly associated with lower systolic (p = 0.011) and diastolic blood pressure (p = 0.010). Conclusion: Medication adherence has a more consistent influence on blood pressure control than knowledge level. Hypertension management programs for the elderly should prioritize improving adherence, supported by continuous education integrated with family and community support.